Active surveillance for men with low‐risk prostate cancer. Issue 2 (March 2014) - Sturch, Paul; Kirby, Roger; Challacombe, Ben
Abstract Active surveillance is often advised as an initial management strategy for men with low‐risk localised prostate cancer. In this review the authors examine popular strategies for patient selection, and question whether a more holistic approach could further enhance quality of life and life expectancy. Copyright © 2014 John Wiley & Sons